Persistencia y cambio : acercamientos a la historia de las mujeres en México - Melgar-Palacios, Lucía (El Colegio de México, 2008)
The critical review of political and social history, the analyzes of culture, discourse and daily life from the feminine perspective that are offered here, allow us to also trace the features of gender culture in Mexico. As these studies show, when the point of view is placed on women and everyday, political or social life is illuminated from their own experience, the panorama changes -much or little- but it is always enriched.